2020
DOI: 10.1002/jclp.23075
|View full text |Cite
|
Sign up to set email alerts
|

A practice‐based evidence investigation of God representations in spiritually integrated psychotherapies

Abstract: Objective This practice‐based evidence study examined trajectories of God representations and psychological distress among Christians participating in spiritually integrated psychotherapies (SIPs). Methods In total, 17 clinicians practicing SIPs in a mid‐sized city on the US Gulf Coast implemented session‐to‐session assessments of these outcomes with 158 clients over a 4‐month period and also reported their use of specific spiritual interventions after each session (e.g., affirmed client's divine worth). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
(68 reference statements)
2
22
0
Order By: Relevance
“…Consistent with Smith et al (2007) meta-analytic review, encouraging personal prayer was the most frequently used spiritual intervention in the present study across the entire sample. In addition, similar to other studies conducted in the U.S. (Currier et al, 2021; Sanders et al, 2015), affirming trusting God and encouraging clients to listen to their hearts were common spiritual interventions.…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with Smith et al (2007) meta-analytic review, encouraging personal prayer was the most frequently used spiritual intervention in the present study across the entire sample. In addition, similar to other studies conducted in the U.S. (Currier et al, 2021; Sanders et al, 2015), affirming trusting God and encouraging clients to listen to their hearts were common spiritual interventions.…”
Section: Discussionsupporting
confidence: 66%
“…Five studies examined SERT integration more broadly within psychotherapy, suggesting the clinical relevance of SIPs for a variety of presenting concerns. Utilizing session-to-session assessments with 158 Christian patients over 4 months, Currier et al (2021) found nearly all patients wanted SERT engagement, which therapists provided using a variety of spiritual intervention strategies. Patients who developed more benevolent God representations had a greater likelihood of experiencing symptom alleviation.…”
Section: Synthetic Review Of the Practice-based Evidencementioning
confidence: 99%
“…Thus, we utilized a qualitative approach to assessing religious attachment in an effort to elucidate culturally and theologically specific ways of viewing and experiencing God in a particular religious group (i.e., Christian clients). The specific research questions we sought to explore were: and December 2019 (for details about recruitment and other procedures from the practice-based evidence project, see Currier et al, 2020). In addition to session-to-session outcome monitoring, clients completed a questionnaire consisting of qualitative and quantitative assessments that provided a more in-depth picture of their religious attachment.…”
Section: Study Aims and Questionsmentioning
confidence: 99%
“…Longitudinal studies with treatment‐seeking samples have affirmed the clinical importance of God representations in spiritually integrated psychotherapies. Session‐to‐session outcomes from the project on which this study is based revealed that clients generally displayed stable‐high trajectories of benevolent God representations (Currier et al, 2020). Further, this parent study found clients who increased in their benevolent representations of God had a greater probability of alleviation of psychological distress.…”
Section: God Representations In Spiritually Integrated Psychotherapiesmentioning
confidence: 99%